2015
DOI: 10.1186/s12887-015-0527-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Family Integrated Care model of neonatal intensive care: a cluster randomized controlled trial in Canada and Australia

Abstract: BackgroundAdmission to the neonatal intensive care unit (NICU) may disrupt parent-infant interaction with adverse consequences for infants and their families. Several family-centered care programs promote parent-infant interaction in the NICU; however, all of these retain the premise that health-care professionals should provide most of the infant’s care. Parents play a mainly supportive role in the NICU and continue to feel anxious and unprepared to care for their infant after discharge. In the Family Integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 52 publications
3
95
0
6
Order By: Relevance
“…6 Thus, the insertion of the family, especially of the parents, in the care of the NB is essential, since they play a fundamental role in the recovery of the baby. 12 The results of this study corroborate this idea, since they demonstrated that the majority of mothers evaluated in a positive way the item on the incentive of professionals for them to take care of their own children.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…6 Thus, the insertion of the family, especially of the parents, in the care of the NB is essential, since they play a fundamental role in the recovery of the baby. 12 The results of this study corroborate this idea, since they demonstrated that the majority of mothers evaluated in a positive way the item on the incentive of professionals for them to take care of their own children.…”
Section: Discussionsupporting
confidence: 76%
“…[10][11] Other researches have also shown that the care centralized in the family promotes a better integration of parents with the newborn, which can reduce this abrupt distancing caused by hospitalization in the neonatal environment. 6,12 However, studies have shown that there are still many aspects related to the humanization of care that need to be improved, and there are many obstacles encountered by professionals in offering this kind of assistance, such as lack of infrastructure, flexibilization of visiting hours so as to meet not only the needs of the sector, among others. [13][14] In this way, mothers need a more frequent and closer assistance before this new phase of their life: the experience of hospitalization of their baby in a Neonatal Unit.…”
Section: Introductionmentioning
confidence: 99%
“…FICare incorporates evidence‐based practices with strong evidence including parent education and psychosocial support, peer‐to‐peer support, clinical team education (with special emphasis around communication with families), and environmental supports including physical and procedural supports for prolonged parental presence. A key tenet of the implementation of FICare is that FICare's implementation needs to be co‐led by parents and the clinical team, making FICare adaptable to the needs of different environments, while maintaining fidelity to its core pillars (Bracht et al, ; O'Brien et al, ). Different strategies and tools may need to be used for different environments depending on their structure and the available resources.…”
Section: Discussionmentioning
confidence: 99%
“…Parents are resident in the neonatal intensive care unit for extended periods, learn to provide all care (except intravenous fluid and medications), record observations in medical charts, and participate in ward rounds, with their involvement underpinned by peer support and education. 2 FICare has been in use since the late 1980s in Estonia 3 and low-resource settings; 4 however, there has been a paucity of robust evidence to support it.…”
mentioning
confidence: 99%